Public Procurement for Innovation in Greece - Tsipouri, L.; Athanassopoulou, S. (Public procurement for innovation policy: International perspectives, 2014)
This paper analyses the experiences and potential for public procurement targeting innovation (PPfI) and pre-commercial public procurement (PCP) in Greece, which is a country with small internal market skewing actual activities towards light manufacturing, labour-intensive industries and small-firm organisation. This environment is not conducive to PPfI, as there is limited lobbying power and few visible impacts from it. Public procurement is in general organised in a traditional way, respecting the EU Directives but not acting as an industrial policy tool. It is, however, argued that even in such markets diffusion-oriented PPfI and unintentional PPfI can play a beneficial role and create potential benefits from export markets, when co-development of client and supplier is successful, in particular if this takes place early in the technology cycle to allow suppliers to acquire knowledge about specific business procedures and be able to demonstrate systems in operation.